ANALISA SPASIAL DAERAH PENANGKAPAN IKAN DENGAN ALAT TANGKAP JARING INSANG (GILL NET) DI PERAIRAN KOTA SEMARANG PROVINSI JAWA TENGAH - Cristianawati, Olvi; M.Pi., Pramonowibiwo; Hartoko, Agus (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Central Java fishery is dominated by fish resources which are caught from the sea. Fish resources potential in Semarang Sea is about 1.873.539 ton/ year and it is divided into two sea territories such as Java Sea and Indonesian Ocean. In general, coastal communities in Central Java have a job as a fisher. One of the fishing gear are widely used and operated that can be called Gillnet. The utilization of fish resources as food source should be followed by sophisticated tools and technological improvements with the use of remote sensing technology. The purpose of this study is mapping fishing areas and researching the spatial fishing ground with gillnets in Semarang Sea Territory Central Java. In this research, the writer used explorative method. Explorative method has some purposes for knowing a social phenomenon about the relation between two or more variables. For taking some samples, the writer used purposive sampling method. The results from this research produced a map of the fishing that show gillnet gear dominantly in coastal and offshore areas. The gillnet makes some operation in coastal areas and it operates drift gillnet in the depth of 1 – 3 meters with the product such as: Pennahia sp, Restreligger sp, Scomberoides sp, Portunus sp, Plofosus sp, Lates sp, Scylla sp, Himantura sp, Polynemus sp, parastromateus and Siganus sp, encircling gillnet. In the depth of 5 meters gets the products such as: Mugil sp, Penaeus sp, Rochteichthys sp and drift gillnet in offshore areas in the depth of 25 – 30 meters with the products like: Scomberomorus sp, Euthynus sp, Xiphias sp.